2017
DOI: 10.1093/ehjci/jex102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of statins on plaque rupture assessed by optical coherence tomography in patients presenting with acute coronary syndromes: insights from the optical coherence tomography (OCT)-FORMIDABLE registry

Abstract: Chronic pre-treatment with statins is associated with a reduced prevalence of ruptured plaques in patients presenting with ACS, particularly in those with NSTE-ACS. Statins bear hence the potential to reduce morbidity during the acute phase of ACS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
1
23
0
Order By: Relevance
“…In combination, these results suggested that hyperglycemia has a strong association with vulnerable plaque characteristics, namely, plaque rupture, lipid-rich plaque, and TCFA, regardless of DM status. It is worth mentioning that pretreatment with statin before acute coronary syndrome reduces not only the presentation of STEMI but also the prevalence of ruptured plaque and TCFA [24]. In the present study population, 18.7% of non-DM patients and 13.7% DM patients were on statin therapy before the index STEMI (p = 0:293).…”
Section: Culprit Lesion Characteristics In Nondiabetic Stemimentioning
confidence: 62%
“…In combination, these results suggested that hyperglycemia has a strong association with vulnerable plaque characteristics, namely, plaque rupture, lipid-rich plaque, and TCFA, regardless of DM status. It is worth mentioning that pretreatment with statin before acute coronary syndrome reduces not only the presentation of STEMI but also the prevalence of ruptured plaque and TCFA [24]. In the present study population, 18.7% of non-DM patients and 13.7% DM patients were on statin therapy before the index STEMI (p = 0:293).…”
Section: Culprit Lesion Characteristics In Nondiabetic Stemimentioning
confidence: 62%
“…Increased plaque instability may be the cause of the incidence of AF, together with smoking, drinking, and older age. Long-term treatment with statins is related to decreased occurrence of plaque rupture detected by OCT in patients presenting with ACS, with a potentially more marked effect in patients with NSTE-ACS [ 33 ]. Statins can enhance the production of endothelial-derived NO synthase, increase coronary blood flow, and reduce ischemia reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“… 7 48–50 It has also been shown that accumulation of apo C-III and triglycerides in the necrotic core predisposes to plaque vulnerability in patients with stable CAD 51 ; hence, the significant lowering effect of fenofibrate on both of these parameters might justify its potential efficacy in preventing plaque rupture and acute CV events, as shown for statin therapy. 52 In addition, there is evidence in vivo showing the stabilising and regressing effects of fenofibrate 53 54 on the atherosclerotic plaque. It has been shown that elevated triglycerides and low HDL-C are not only associated with macrovascular atherosclerotic changes such as CAD, but they are also risk factors for microvascular disease in type 2 diabetes mellitus.…”
Section: Discussionmentioning
confidence: 99%